NCOG-11. NEUROPSYCHOLOGICAL OUTCOMES FOLLOWING AWAKE CRANIOTOMY FOR LOW GRADE GLIOMA. (11th November 2019) - O'Hara, Daniel; Miller, Amy; Goodden, John; Graham, Christopher; Kitchingman, Hayley; Mathew, Ryan; Richards, Oliver; Chumas, Paul
Abstract: BACKGROUND: Awake craniotomy is an established treatment for tumours in eloquent brain regions. It aims to achieve maximal resection without significant neurological and functional morbidity. There is an emerging evidence base about the neuropsychological outcomes following awake craniotomy for low grade gliomas (LGGs) with inconsistent findings potentially reflective of methodological confounders such as the inclusion of mixed tumour types and the use of varied neurocognitive measures and timescales for repeat testing. We describe detailed neuropsychological outcomes for a cohort of patients following awake craniotomy for LGGs. METHOD: Data were collected from patients undergoing first-time awake resection of presumed LGGs at Leeds Teaching Hospitals, UK between 2010 and 2018. Patients were included if they consented to and completed the full battery of pre- and postoperative neuropsychological testing. Neuropsychometric testing involved assessment of general intellectual functioning, language, memory, executive functioning, perception, processing speed and mood. Data were analysed using paired-samples t-test or Wilcoxon signed-rank test with Bonferroni correction for multiple statistical comparisons. RESULTS: Twenty-two patients undergoing awake craniotomy for presumed supratentorial LGG (13 left hemisphere, 9 right hemisphere; mean age 35 years) met the above inclusion criteria. Tumour location was heterogenous (11 insular, 9 frontal, 1 temporal, 1 parietal). Histopathology confirmed WHO Grade II diffuse astrocytoma (n=11), WHO Grade II oligodendroglioma (n=10) and WHO Grade III anaplastic oligodendroglioma (n=1). No statistical differences in neurocognitive test scores were found pre- and post-neurosurgery (mean follow-up was 61 weeks). Other outcomes including extent of resection and reliable change statistics for neurocognitive tests and measures of mood were also analysed. CONCLUSION: No significant change in neurocognitive functioning was found in patients following recovery from awake craniotomy for LGG. Our findings suggest that awake craniotomy is a safe treatment for LGG and that neuropsychological input is an important part of the treatment pathway for patients with LGG.